The Influence of Political Connections, Firm Size, and of Women on Board to Return on Assets in Food and Beverage Companies Listed in Indonesia - Indra Mufid; Khalida Kumalasari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this research is to investigate the influence of political connections, firm size, and the presence of women on the Return on Assets (ROA) of Food and Beverage companies in Indonesia.. The type of research conducted is quantitative, utilising secondary data. The sample analysed consists of 63 companies with an observation period from 2020 to 2024, employing panel data analysis techniques through Eviews v.22 software.. The findings indicate that, partially, the variables of political connections, firm size, and the presence of women positively influence the Return on Assets of Food and Beverage companies in Indonesia. Political connections, firm size, and the women on board have a positive impact on the Return on Assets of companies. Employees with political access contribute to better decision-making. Larger companies with comprehensive indicators tend to experience increased revenues. The women on board within the corporate structure leads to more mature decisions, thereby enhancing the quality of decision-making.